The switching mechanism of the bacterial rotary motor combines tight regulation with inherent flexibility. (23rd February 2021) - Afanzar, Oshri; Di Paolo, Diana; Eisenstein, Miriam; Levi, Kohava; Plochowietz, Anne; Kapanidis, Achillefs N; Berry, Richard Michael; Eisenbach, Michael
Abstract: Regulatory switches are wide spread in many biological systems. Uniquely among them, the switch of the bacterial flagellar motor is not an on/off switch but rather controls the motor's direction of rotation in response to binding of the signaling protein CheY. Despite its extensive study, the molecular mechanism underlying this switch has remained largely unclear. Here, we resolved the functions of each of the three CheY‐binding sites at the switch in E. coli, as well as their different dependencies on phosphorylation and acetylation of CheY. Based on this, we propose that CheY motor switching activity is potentiated upon binding to the first site. Binding of potentiated CheY to the second site produces unstable switching and at the same time enables CheY binding to the third site, an event that stabilizes the switched state. Thereby, this mechanism exemplifies a unique combination of tight motor regulation with inherent switching flexibility. SYNOPSIS: Flagellated bacteria like E. coli change their behaviour from swimming to tumbling by altering the direction of flagellar motor rotation. Here, this directional change is shown to involve sequential interactions of the ligand, CheY, with its three binding sites at the motor, each with a different outcome. The motor employs one binding site to capture its ligand, phosphorylated CheY, and potentiate its motor switching activity. A second site binds potentiated CheY to bring the motor into an unstable switched state. This interaction with the second site exposes a third binding site. Binding of acetylated CheY to the third site stabilizes the motor in the clockwise‐rotation state. Abstract : A three‐step mechanism of CheY binding to the E. coli flagellar motor switches bacterial swimming behavior from swimming to tumbling to enable chemotaxis.